2014
DOI: 10.1002/eqe.2520
|View full text |Cite
|
Sign up to set email alerts
|

Proposed design models for the asymmetric friction connection

Abstract: SUMMARYThe Asymmetric Friction Connection (AFC) remains elastic during moderate earthquake shaking but slides and dissipates energy through friction during severe earthquake shaking. The sliding friction forces developed are dependent on the clamping force in the connection which is provided by fully tensioned bolts which pass through slotted holes. During sliding these bolts are subject to moment and shear as well as axial force. Moment-shear-axial force interaction reduces the clamping axial force on the sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 21 publications
(44 reference statements)
0
51
0
Order By: Relevance
“…The column base uplift displacement, Δ Uplift , is given by Eq. (12), where c Tens is the distance perpendicular to the neutral axis to the extreme fibre of the section on the gapping side as shown in Fig. 9.…”
Section: Analytical Prediction Of Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The column base uplift displacement, Δ Uplift , is given by Eq. (12), where c Tens is the distance perpendicular to the neutral axis to the extreme fibre of the section on the gapping side as shown in Fig. 9.…”
Section: Analytical Prediction Of Performancementioning
confidence: 99%
“…The main objective of these studies was to find materials that can provide a stable performance of friction connection. Chanchí et al [4], Loo et al [19], and Khoo et al [12] tested friction components under low cycle fatigue to many cycles of loading in regard to what they will experience in an earthquake, and no low cycle fatigue was reported. These tests have been for numbers of cycles of loading well in excess of what they have encountered in practice.…”
Section: Introductionmentioning
confidence: 98%
“…The ductile performance of the SBC is remarkable, dissipating significant amount of seismic energy [23,24]. FitzGerald et al [15] concluded two states of the SBC performance, where the first state was the friction state with no strength hardening and the second state included the strength hardening at a larger deformation level.…”
Section: Introductionmentioning
confidence: 98%
“…Loo et al proposed a type of symmetric slip–friction connector where the expensive brass shims were eliminated. Extensive researches on SBCs were done at University of Auckland by Butterworth, Clifton, and their co‐workers, who developed the semi‐rigid sliding hinge joint and its friction damper, namely the asymmetric friction connection. In addition to the rotational SBCs, the shear SBCs, which are applied to the center of the beam, have been proposed recently to improve the shear force resistance for generalized lateral load‐resisting systems, where the shear SBCs act as a mechanical shear fuse demonstrating reliable seismic behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the seismic performance, experimental studies have demonstrated that SBC components are able to dissipate significant amounts of energy . Existing studies found that a typical SBC usually demonstrate force pinching phenomena due to contact phenomena and plastic deformation .…”
Section: Introductionmentioning
confidence: 99%